Comparative Economics of Rice Cultivation in Himachal Pradesh and Manipur States of India - Yumnam, Anjoo; Kumar, Ashok; Chauhan, S. K. (Indian Journal of Hill Farming, 2018)
Rice is an important food crop of India and with almost no scope in increasing the area under this crop and recent trends of declining growth rates and increasing shortages ininputs, the aim should be at eliminating the spatial differences in yield and production to augment rice production. Due to various differences, the average yield of paddy are quitedifferent between Himachal Pradesh (1.55 t/ha) and Manipur (2.26 t/ha). Therefore, the present study was conducted in Kangra district of Himachal Pradesh and Imphal-Westdistrict of Manipur to compare the economics of rice cultivation in the two states during the growing season of 2011-12. Stratified simple random sampling technique was used toselect 50 paddy growing farmers from each district and then categorised into small and large farmers. Gross returns were found to be higher on large farms than on small farms inboth the states. Small farms of Manipur were not viable, as the price they received for a quintal of the main product (Rs 1200) did not cover the cost of production (Rs 1202).Cobb-Douglas production function analysis revealed that the factors affecting paddy production on small farms were use of manures and fertilizers and plant variety in Himachal Pradesh and use of seed and plant variety in Manipur. The factors responsible for paddy production on large farms were use of seed, plant protection chemicals and plant variety in Himachal Pradesh, while they were use of manures and fertilizers, seed, plant protection chemicals and plant variety in Manipur.